Photocatalytic degradation of malachite green pollutant using novel dysprosium modified Zn–Mg photocatalysts for wastewater remediation. Issue 19 (1st October 2022) - Jasrotia, Rohit; Suman; Verma, Ankit; Verma, Ritesh; Godara, Sachin Kumar; Ahmed, Jahangeer; Mehtab, Amir; Ahmad, Tokeer; Puri, Pooja; Kalia, Susheel
Abstract: The malachite green dye is an exceedingly dangerous pollutant, and it is suspected of causing illnesses including cancer, mutational instability, and pulmonary toxicity. This study reported the successful fabrication of undoped and Dy 3+ doped Zn–Mg nanophotocatalysts by the sol-gel auto-combustion approach. We studied their structural, morphological, optical, magnetic, and photocatalytic degradation characteristics. The XRD patterns of fabricated photocatalysts showed the formation of spinel cubic-like crystal structure with Fd3m space geometry. No extra impurity phases were seen in the observed diffraction patterns. The crystallite size (45.07–53.51 nm) was calculated using the Debye-Scherrer formula from the (311) intense peak of XRD diffraction patterns. The FESEM images of ZM1 and ZM3 nanoferrites show the existence of spherical grains with well-defined grain boundaries. In the preparation of ZM1, ZM2, and ZM3 nanoferrites, the band gap values decreased from 2.34 eV to 2.18 eV with increasing Dy 3+ content. FTIR investigation confirmed the stretching vibrations between the metal and oxygen ions at the tetrahedral and octahedral sites. Four Raman active frequency bands were present in the Raman study from 180 to 800 cm −1 . The magnetic study of prepared samples revealed the formation of magnetic nanophotocatalysts with an excellent saturation magnetization of 6.72–9.74 emu/g. The undoped and doped photocatalysts were utilized to degrade the malachite green dye under natural sunlight. The ZM3 nanoferrite shines above all the other photocatalysts with a maximum photocatalytic degradation efficiency of 94.23%. The nanoferrites can be readily separated using an external magnet. Thus, the produced nanoferrites with high degradation efficiency are appropriate for the wastewater treatment application.